An efficient algorithm for the global modeling of RF and microwave circuits using a reduced nonlinear lumped network (RNL/sup 2/N)-FDTD approach - Mrabet, O.E.; Essaaidi, M. (IEEE microwave and wireless components letters, 2004)
In this letter, we present an efficient and simple reduced nonlinear lumped network (RNL/sup 2/N)-FDTD method for the global modeling of RF and microwave circuits. This method is a simplified version of the original nonlinear lumped network (NL/sup 2/N)-FDTD approach, which does not require a complicated precalculation and a huge back-storage compared to the former version.